The Exploitation of the Traditional Component in Restructuring Modern Food Offer in Romania - Magdalena Bobe; Roxana Procopie; Maria Alexandra Toma (Amfiteatru Economic)
Food and eating habits, together with adjacent agricultural activities have had and an important role in the development of modern society and the individual itself. Besides its nutritional role, food has become a main socio-cultural determinant, food consumption patterns being influenced, on one hand, by psycho-sensory and quality characteristics of the food product and, on the other hand, by the physiological state of the consumer and its main determinants: traditions, religion and culture. These elements, together with economic considerations have a significant share in shaping the modern eating habits. In this context, the present paper aims to identify and analyze the main capitalization methods of the food’s traditional potential in reshaping the modern food offer, starting with a literature review and continuing with an exploratory analyze of the traditional food sector in Romania. Considering the main directions outlined by literature, this article tries to identify a set of specific features of the traditional food sector in Romania both in terms of producer and consumer perspectives. In this regard, an interview and an exploratory based questionnaire study were conducted. Having as a starting point the wide variety of Romanian food resources, this study aims to highlight how culinary customs have been modeled throughout history in order to establish eating patterns as an assessment method based on the impact of technological progress on the future alimentation.